La cátedra de bibliografía jurídica de la Universidad Central de Madrid (1883-1936) - Villaseñor Rodríguez, Isabel (Revista General de Información y Documentación, 2007)
The text talks about the experience that, during some years, one came giving in the Ability of Right of the Central University of Madrid, with the purpose of forming the students of Doctorate in the handling of the most appropriate sources of information for the knowledge of the matters that conformed the plan of studies. The components are exposed that gave place to their creation, as well as their development, analyzing the different changes that it experienced in their denomination and the profile of each one of the professors that were to their position, the same as the manuals published as complement to the educational activity in the classrooms.